2017
DOI: 10.1111/jpim.12434
|View full text |Cite
|
Sign up to set email alerts
|

Elevating Design in the Organization

Abstract: Following evidence of its positive contribution to innovation and company performance, many firms are seeking to elevate design to a strategic level. However, little is known as to how this can be achieved. This study draws on the literatures concerned with elevating organizational functions and with organizational legitimacy, and aims to unravel and detail critical practices and potential tensions influencing the elevation of design's status in firms. To do so, 53 in‐depth interviews were undertaken with key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 69 publications
0
64
0
Order By: Relevance
“…Recent literature suggests that if enduring and sustained attention for a topic is an indication of its value, then Design Thinking merits considerable further scrutiny [1]. The motivation for this paper is to add to the recent scholarship on Design Thinking, but also to contribute to the foundation of an emerging dimension of Design Thinking: Art Thinking [2].…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature suggests that if enduring and sustained attention for a topic is an indication of its value, then Design Thinking merits considerable further scrutiny [1]. The motivation for this paper is to add to the recent scholarship on Design Thinking, but also to contribute to the foundation of an emerging dimension of Design Thinking: Art Thinking [2].…”
Section: Introductionmentioning
confidence: 99%
“…This work is concerned with where design thinking should be located within the organizational structure 33 and also considers how design can be elevated to a strategic level in organizations. 34 and formalization of product and service development processes. 35 They suggest that strategic design is more effective when designers operate cross-functionally because it enables designers to better balance the role of design champions alongside commercial considerations.…”
Section: Design and The Structural Aspects Of Strategic Managementmentioning
confidence: 99%
“…34 and formalization of product and service development processes. 35 They suggest that strategic design is more effective when designers operate cross-functionally because it enables designers to better balance the role of design champions alongside commercial considerations.…”
Section: Design and The Structural Aspects Of Strategic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature on increasing the contribution of design, different models and frameworks can be found. For example, various models have similarly considered design as capability or as resource (Acklin, 2013;DDC, 2003;Kootstra, 2009;Westcott et al, 2013), as a contributor to branding and firm strategy (M. Beverland & Farrelly, 2007), as requiring cross-firm acceptance and cross-functional collaboration (Bilson & Aitchison, 2016;Micheli, Perks, & Beverland, 2018), and as process guided by design maturity models with various measurement metrics (Acklin, 2013;DDC, 2003;Kootstra, 2009;Westcott et al, 2013). Micheli et al (2018) found critical success factors for increasing industrial design contribution to a strategic level to include: top management support, leadership of the design function, generating awareness of design's role and contribution, inter-functional coordination, evaluation of design, and formalisation of product and service development processes are all necessary ingredients.…”
Section: Benefits Of Bsc That Are Potentially Shared By Balanced Scormentioning
confidence: 99%